2015
DOI: 10.1017/ppr.2015.4
|View full text |Cite
|
Sign up to set email alerts
|

A Non-local Source of Irish Chalcolithic and Early Bronze Age Gold

Abstract: Lead isotope analyses of 50 Irish Chalcolithic and Early Bronze Age gold artefacts favour a gold source in southern Ireland. However when combined with major element analysis, the artefacts are not consistent with any Irish gold deposit analysed to date. Understanding the lead isotope signatures of ore deposits within a study region allows informed inferences to be drawn regarding the likelihood that an unanalysed ore deposit was exploited in the past. If an Irish gold source is assumed, then the gold is most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 59 publications
1
16
0
2
Order By: Relevance
“…However, the mining of low grade tin ores containing higher levels of haematite, followed by through beneficiation by hand, could also have occurred with similar consequences for archaeological visibility (Yener and Vandiver, 1993). gold objects in Ireland demonstrating non-local sources (Standish et al, 2015). This does not mean that gold sources in Ireland were not exploited during this period -as has been argued for the Mourne Mountains, Ireland -and the prospecting for gold may also have been accompanied extraction of tin (Warner et al, 2010a(Warner et al, , 2010b.…”
Section: Tin Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mining of low grade tin ores containing higher levels of haematite, followed by through beneficiation by hand, could also have occurred with similar consequences for archaeological visibility (Yener and Vandiver, 1993). gold objects in Ireland demonstrating non-local sources (Standish et al, 2015). This does not mean that gold sources in Ireland were not exploited during this period -as has been argued for the Mourne Mountains, Ireland -and the prospecting for gold may also have been accompanied extraction of tin (Warner et al, 2010a(Warner et al, , 2010b.…”
Section: Tin Productionmentioning
confidence: 99%
“…The use of lead isotope analysis as well as trace element analysis in analysing the provenance of tin has suggested that the Uluburun tin ingots contain at least two groups, and tin ingots from Hishuley Carmel off the Israeli coast may have been from the same source as one of the Uluburun groups (Stos-Gale et al, 1998) and also that the Sardinian tin objects were not produced locally (Valera and Valera, 2003).The future use of lead and tin isotope analyses could well provide further insights into the provenance of the Salcombe ingots (cf. Haustein et al, 2010;Standish et al, 2014Standish et al, , 2015.…”
Section: Compositions Of Tin From Different Sitesmentioning
confidence: 99%
“…The source of the gold may again be Iberian, although Cornwall is also a possibility (Taylor , 235–6; O’Connor ; Fitzpatrick , 48; Standish et al . ). Early copper mining at Ross Island in Ireland can be linked to Iberia, depending as it did on fahlerz ores of arsenicated copper.…”
Section: Patterns In the Archaeologymentioning
confidence: 97%
“…No se ha abordado el estudio sobre la procedencia del oro debido a las limitaciones, técnicas y económi-cas, además de la caracterización de las posibles áreas fuentes que todavía en la actualidad persisten (Pernicka 2014), si bien se han realizado notables avances en este campo mediante el análisis de isótopos del plomo (Standish et al 2015).…”
Section: Análisis Arqueométricounclassified